Analisis Faktor-Faktor Pengelolaan Keuangan Daerah Pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Manggarai Tahun 2019-2023 - Apriana H. J. Fanggidae; Siprianus G. Tefa; Dylan Baptista Varani Tatu (Kajian Ekonomi dan Akuntansi Terapan, 2024)
This study aims to analyze the factors affecting regional financial management at the Department of Population and Civil Registration of Manggarai Regency during the 2019-2023 period. The research method used is a mixed-method approach, combining qualitative and quantitative analysis. Data were obtained through interviews, observations, and document analysis. The results indicate that regional financial management is influenced by economic, effectiveness, and efficiency factors. This research is expected to provide recommendations to improve the financial management performance in the relevant agency.